2023
DOI: 10.1038/s41467-023-41743-3
|View full text |Cite
|
Sign up to set email alerts
|

Sampling-based Bayesian inference in recurrent circuits of stochastic spiking neurons

Wen-Hao Zhang,
Si Wu,
Krešimir Josić
et al.

Abstract: Two facts about cortex are widely accepted: neuronal responses show large spiking variability with near Poisson statistics and cortical circuits feature abundant recurrent connections between neurons. How these spiking and circuit properties combine to support sensory representation and information processing is not well understood. We build a theoretical framework showing that these two ubiquitous features of cortex combine to produce optimal sampling-based Bayesian inference. Recurrent connections store an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…Such recurrent excitatory connectivity may seem unintuitive from a normative stand-point, as it amplifies noise [20] and can increase response times [21, 22]. Previous studies suggested that it may support persistent activity and thus working memory [23, 24] and that it may implement complicated priors [25].…”
Section: Introductionmentioning
confidence: 99%
“…Such recurrent excitatory connectivity may seem unintuitive from a normative stand-point, as it amplifies noise [20] and can increase response times [21, 22]. Previous studies suggested that it may support persistent activity and thus working memory [23, 24] and that it may implement complicated priors [25].…”
Section: Introductionmentioning
confidence: 99%